Analysis Of Heat Generation During Friction Stir Processing of Aluminium Similar Joints - Mishra, Akshansh; Sharma, Abhishek Kumar (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
In this paper, the study of heat generation during friction stir processing of similar joints of AA6061-T6 is carried out. A three dimensional (3D), transient, a non-linear thermal model was developed using ANSYS 16.2 software to simulate the heat generation profile during Friction Stir Processing of similar Aluminium plates. The results showed that the observed temperature rise in the model shows that heat generated during the second and third load steps is due to friction between the tool shoulder and workpiece, as well as plastic deformation of the workpiece material. It was also observed that friction is responsible for generating most of the heat needed, while the contribution of heat due to plastic deformation is less significant. Because the tool-penetration in the workpiece is shallow, the heat generated due to tool pin is ignored and the plastic heat generated is small compared to frictional heat.